TINJAUAN YURIDIS PERJANJIAN SEWA MENYEWA UNIT HUNIAN RUMAH TOKO (RUKO) BERDASARKAN PASAL 1338 KITAB UNDANG-UNDANG HUKUM PERDATA DI KOTA SAMARINDA - Syilvia Hestiani (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTBasic needs of every human being in life is to take clothing, food and shelter. To achieve the welfare of the coveted by every human being, then the first requirement must be fulfilled for clothing, food and shelter for every human being is, in order to live in peace in accordance with the craved. Basic needs in the areas of board (home) as the top priority of every human being, because the house is the residence that serves, among others, as a shelter, educate and nurture domestic life and interact with other families in order to organize a better life and to achieve prosperity desired.The availability of land for housing is very limited and very expensive. Then the solution offered is the construction of housing with vertical systems commonly called flats. However modest apartment rental utilization should be based on a lease agreement homes, apartment units that can be rented flats are located in the management and supervision of local governments that builds on the Local Government Budget and Central Government for the sake of helping people who do not have a place to stay and one forms of public welfare purposes.